Dilema Yuridis Rehabilitasi Presiden Terhadap Vonis Korupsi: Analisis Paradigmatik dan Rekomendasi Kebijakan - Yuherman (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper critically examines the legal dilemma arising from the presidential rehabilitation granted to former PT ASDP Director Ira Puspadewi, a convicted corruption defendant, which epitomizes the profound tension between the positivist principle of final court decisions as pillars of legal certainty and the realist intervention of executive prerogative to achieve substantive justice. Employing a normative-juridical methodology analyzed through the dual lenses of Legal Positivism and Legal Realism, the study dissects this conflict between law as codified rule and law as a social instrument. The findings reveal that while procedurally anchored in Article 14 of the 1945 Constitution, the act creates systemic inconsistency in anti-corruption enforcement and dangerously blurs the line between criminal misconduct and permissible business judgment risk within State-Owned Enterprises. Consequently, it is concluded that such ad-hoc resolutions undermine long-term legal predictability. To resolve this, a triad of integrated policy reforms is recommended: the urgent codification and limitation of the presidential rehabilitation prerogative through specific legislation, the explicit integration of the Business Judgment Rule doctrine into the SOE and anti-corruption legal framework to shield good-faith corporate decisions, and the establishment of a transparent mechanism, potentially under the Supreme Court, to publish binding and accountable considerations for any prerogative use, thereby ensuring future actions are both just and systematically consistent.